Peningkatan Aktivitas dan Hasil Belajar Menyimak Pidato dengan Metode TPS-R pada Siswa Kelas IXA SMP Negeri 2 Mataram - Utomo, Wasis (TSAQOFAH, 2023)
This research was conducted to determine the increase in activity and achievement of class IXA students of SMP Negeri 2 Mataram in listening to speeches using the TPS-R method. This Classroom Action Research uses two cycles with each cycle implementation covering (a) planning action (planning), (b) implementing action (acting), (c) observing (observing), (d) reflecting (reflecting). While the research procedure includes the steps: (1) preparation, (2) initial study/survey, (3) implementation of the cycle, and (4) preparation of reports. The results of the data analysis showed that the activity and achievement of class IXA students at SMP Negeri 2 Mataram in listening to speeches increased. Researchers took action in two cycles, in cycle I it was seen that the percentage of student test scores reached 79%. This shows that students have not fully achieved learning mastery. Whereas in cycle II the percentage of student tests has increased to 96%. This shows that there is an increase in the percentage of student learning completeness. This increase was partly due to an increase in students' motivation and creativity in learning. This indicates an increase in learning outcomes in the material for listening to speeches in Indonesian lessons. Although basically the use of the TPS-R method in learning is not the only method that can be used in Indonesian subjects, this method can help students understand the material listening to speeches. However, this also needs to be supported by the willingness of students to study poetry more actively so that it can be applied in everyday life. Based on the results obtained by students in cycle II, this research was declared successful in achieving the research objectives to be achieved.